Lawsuits & Rulings. Issue 12 (April 2017) - Unknown
Abstract : Racial Discrimination: Lack of evidence dooms former police officer's suit Sexual Harassment: Minor slights don't justify suit over sexual harassment Athletics: Assaulted player cannot sue university